Pengaruh Kekayaan Daerah Dan Belanja Modal Terhadap Kinerja Penyelenggaraan Pemerintah Daerah: Pengujian Kompleksitas Pemerintah Sebagai Variabel Moderasi - Megawati Sukarni Putri; Vita Fitria Sari (Universitas Negeri Padang, 2020)
This study aims to examine the effect of regional wealth and capital expenditure on the performance of local government administration, and to see whether government complexity will affect the relationship betwen regional wealth and capital expenditure on the perfomance of local government administration. Population in this study were districts/cities in West Sumatera Province in 2013-2017. The analytical tool used in this study is moderate regression analysis. The results of this study indicate that regional wealth doesn’t affect the performance of local government administration, and capital expenditure negatively affects the performance of local government administration. Government complexity doesn’t moderate the relationship between regional wealth and capital expenditure on the performance of local government administration. The results of this study also show that complexity of the government weakens the relationship between regional wealth and capital expenditure on the performance of local government administration